Dos nuevas variedades de yuca de alta produccion para los Llanos Orientales - Rodríguez H, N.S.; Hershey, Clair H. (Instituto Colombiano Agropecuario, 1990)
Information is presented on 2 cassava var., ICA-Catumare and ICA-Cebucan, released by the Instituto Colombiano Agropecuario and CIAT, for the Colombian Llanos Orientales. ICA-Catumare originates from the cross between regional var. Guajiba and CMC-86. ICA- Cebucan originates from the cross between 2 hybrid clones, Chiroza Yema de Huevo and MVEN 218. Yields were 24.0 and 22.2 t/ha for ICA- Catumare and ICA-Cebucan, resp., in the piedmont region whereas yields of these var. were 14.7 and 20.4 t/ha for the high tablelands. ICA-Catumare is resistant to bacterioses and superelongation, intermediately resistant to blight leaf spot, and susceptible to root and stem rot; it also shows intermediate resistance to mites, thrips, and lace bugs. ICA-Cebucan is resistant to bacterioses, blight leaf spot, root and stem rot, and superelongation; it is also resistant to mites, thrips, and lace bugs. Recommendations are also given for the cultivation of both var. (CIAT)